Optimization of banana pseudostem co-compost and sap in enhancing growth, yield and quality of sweet corn under acidic soil - Islam, Mahammad Shariful (2023)
Sweet corn (Zea mays L.) is an emerging and important food crop over the world while in Malaysia, the production is lower than its consumption. The soil of the tropics generally has low pH, and poor nutrient content, with high iron and alumunium that affect crop productivity. By contrast, large quantities of chemical fertilizers are needed to sustain crop production, which then promotes soil degradation. The compost, having high pH, reserve nutrients, and cation exchange capacity may improve soil chemical properties, plant growth, nutrient uptake, and crop yield. Besides, the nutrients and phytochemicals rich banana pseudostem sap can be absorbed faster by the leaf which may overcome the lower efficiency of fertilizer in acidic soil. Four studies were successively executed with the aim (i) to evaluate the chemical changes in the composting of banana pseudostem, mushroom media waste, and chicken manure; (ii) to observe the effects of different rates of compost and foliar spray of banana pseudostem sap on the soil chemical properties, growth, and yield of sweet corn planted in acidic soil; (iii) to identify the phytochemicals, present in banana pseudostem sap and confirm their influential role on the seedling growth; (iv) to evaluate the effect of the enriched banana pseudostem sap on the yield, and quality of sweet corn. The first experiment involved compost production using banana pseudostem (BPS), mushroom media waste (MMW), and chicken manure (CM) at ratios of 1:1:1, 1:2:1, 1:3:1, 2:1:1, 2:2:1, and 2:3:1. Mixing of BPS, MMW, and CM at 1:2:1, 1:3:1, and, 2:3:1 ratios, respectively, demonstrated a longer thermophilic phase, indicating more complete decomposition and earlier maturity as compared to piles 2:1:1 with a double amount of BPS to MMW. Among the ratio, 1:2:1 (BPS:MMW:CM) resulting in pH>10, the highest total nitrogen (1.53%), the lowest C:N ratio (12.4), greater OM degradation (54.5%), maximum nutrients density, and showed no toxicity for seed germination index (129%), as BPS addition to optimize the moisture content in the mixture. In the second experiment, amending compost (control, 5 t ha-1, 10 t ha-1, and 15 t ha-1) and banana pseudostem sap foliar application (control, 2 times and 3 times) were compared with chemical fertilizers in the factorial RCBD setup. Incorporation of 15 t ha-1 compost alone improved the soil pH (1.79 units), total carbon content (0.86-1.62%), cation exchange capacity (4.55-8.2 cmolc kg-1) while for exchangeable acidity (0.32-0.03 cmolc kg-1) and aluminium (0.19-0.02 cmolc kg-1) concentration, it decreased significantly, as compared to chemical fertilizer treatment. Though foliar fertilization has no significant influence on soil properties, it increases potassium, calcium, and magnesium uptake by sweet corn. The amendment of compost @ 15 t ha-1 with three times foliar spray of BPS however improved potassium (888-1803 mg 100g-1), calcium (72-604 mg 100g-1), and magnesium (6.30-91.0 mg 100g-1) uptake over control. The fresh cob yield significantly increased by 13% in 15 t ha-1 compost, and 7% by three times foliar BPS treatments, respectively, over chemical fertilizer application. The third experiment focuses on the identification of beneficial phytochemicals and mineral nutrients in banana pseudostem sap before they can be tested for their stimulatory role on seedling growth (up to 10 days) under different (Control, 5, 10, 15, 25, 50, and 100%) concentrations. The LC-MS analysis has identified 86 phytocompounds where 44 compounds are related to plant growth and development. Among the applied concentrations, 10% aqueous banana pseudostem sap resulted in 32% higher dry biomass, than the control since it contains various amino acids, phenolics, alkaloids, organic acids, and mineral nutrients. Lastly, banana pseudostem sap that was enriched with essential nutrients (N-20, P2O5-15, K2O-15, and B 0.2% per liter sap) and was tested in the field in combination with reduced doses of chemical fertilizers (i.e. 75% chemical fertilizers + non-enriched foliar pseudostem sap and 50% chemical fertilizers + foliar spray of enriched pseudostem sap). Both treatments were then compared with soil-applied chemical fertilizers following the RCB design. The enriched banana pseudostem sap in combination with 50% recommended dose of soil-applied chemical fertilizers increased yield from 13.74-19.16 t ha-1 (39.44%), soluble protein (21.0-24.5 g 100g-1DM) (16.66%), and total soluble sugar (4.46-5.15 g 100g-1DM) (15.47%) over control for nutrient uptake. In conclusion, the utilization of banana pseudostem improved compost quality in the co-composting technique. The use of compost in combination with three times foliar spray of banana pseudostem sap reduced chemical fertilizer use, improving soil properties and sweet corn yield. However, current studies do not explore much on compost humic acid function and specific phytocompounds which are present in banana pseudostem sap. These materials might be useful in improving soil properties and plant growth. Thus, the extraction and quantification of humic substances from mature compost is highly recommended. Besides, a study is also needed related to plant growth-promoting phytochemicals in BPS which could provide significant crop production in acidic soil.